Phytochemical Profiling with Biological Validation Reveals Therapeutic Effect of Vincetoxicum capparidifolium - Prameela, Athira; Krishnasamy, Thenmozhi (Sciences of Phytochemistry, 2026)
The present research discusses the phytochemical composition, anti-inflammatory, antidiabetic, and antiproliferative efficacy of Vincetoxicum capparidifolium leaf aqueous extract. Phytochemical characterization was performed using FTIR and LC-MS analysis. Network pharmacology was employed to identify potential molecular targets of tylophorine associated with liver associated disorders, followed by molecular docking studies. Anti-inflammatory activity and antidiabetic potential was evaluated in vitro. Cytotoxic outcomes were determined using MTT assay on HepG2 cells, along with AO/EtBr staining and DNA fragmentation analysis. FTIR investigation disclosed the occurrence of various functional groups, incorporating hydroxyl, amine, aromatic, and heteroatom-containing moieties. LC-MS profiling categorized a total of 28 compounds belonging to alkaloids, flavonoids, phenols, and fatty acid derivatives. Network pharmacology analysis identified 94 intersecting targets of tylophorine with liver inflammation, diabetic liver disease, and end-stage liver disease, while molecular docking showed binding affinities of tylophorine with proteins, presenting the strongest interaction with 3HHM (-8.9 kcal mol-1). The extract produced concentration-dependent inhibition of protein denaturation (9.5-68.0%), proteolytic activity (10.3-71.7%), and erythrocyte lysis (10.6-70.2%) although its activity was lower than the reference drug, aspirin. The extract also displayed inhibition of α-amylase and α-glucosidase, with greater potency against α-glucosidase (IC50=99.6 µg mL-1). The cytotoxic activity evaluated using MTT assay supported reduction in HepG2 cell viability (IC50=168 µg mL-1). AO/EtBr staining revealed increased apoptotic features, including membrane damage and nuclear condensation, while DNA fragmentation analysis verified apoptosis-mediated cell death. Overall, V. capparidifolium exhibits notable in vitro anti-inflammatory, antidiabetic, and cytotoxic potential, highlighting its potential as a source of bioactive compounds for further pharmacological investigations.